Pengaruh Lingkungan Pesantren Terhadap Kemampuan Hafalan Al-Qur’an Pada Pesantren Tahfizh Darul Qur’an - N, Nurmayani; Deswan, Meisyy Laisa Usrini; Putri, Aulia Kusuma; Septianingsih, Indri Avisa; Putri, Maharani Renika; Jannah, Miftahul; Anggraini, Sepi; Nazwa, Syahira (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the influence of the pesantren environment on the ability to memorize the Qur'an of students at the Darul Qur'an Tahfizh Islamic Boarding School. The study used a qualitative approach with observation and interview techniques in collecting data. The results showed that the pesantren environment provides significant support in the process of memorizing the Qur'an. Factors such as a calm environment, learning policies, measurable memorization targets, and strict regulations help increase the motivation and discipline of students. The conclusion of the study shows that a conducive pesantren environment has a positive impact on the ability to memorize the Qur'an.